Propranolol intervention therapy for infants with facial hemangioma - Meng, Jian; Li, Zhiping; Gu, Qianping; Zhang, Jie; Zhuang, Qianwei; Si, Yameng; Zhang, Aixia (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : The current study aimed to evaluate the clinical efficacy and adverse effects of small doses of propranolol intervention therapy for infants with infantile facial hemangioma in the proliferation stage. Material and methods : A total of 22 patients including 9 males and 13 females with an average age of 5.5 months were enrolled. These patients were diagnosed with facial hemangioma. During the first week of hospitalization, the patients were requested to take propranolol according to their weight (1.0 mg/kg to 1.5 mg/kg once daily). After hospital discharge, the patients were requested to take propranolol consistently and were reassessed every two weeks. We closely observed the process, recorded information about the size, color, and texture of the hemangioma, coped with the adverse effect during the treatment, and evaluated the clinical efficacy of propranolol. Results: The color of the hemangioma faded 24 h after taking propranolol. After 3 months to 9 months of observation, we obtained the following clinical efficacies: level I, 0; level II, 2; level III, 13; and level IV, 7. The effective rate was 100%. The heart rate of 22 patients became slower than before treatment, 2 patients had slight diarrhea that disappeared after treatment, and there was no serious adverse effect during the entire process. Conclusions : With the advantages of minor side effects, convenience, safety, and evident efficacy, the administration of small doses of propranolol is a good method for treating hemangioma in infants.